Fostering digital transformation in the household tools commerce - Trivan, Aleksa; Barać, Dušan (E-business technologies conference proceedings, 2021)
This paper investigates digital transformation of a company that sells wide corpus of tools. Main goal is to provide a comprehensive overview of the digital transformation process and its elements, such as: technologies, human resources, business models and strategies and cooperation. Further, the role of electronic sales channels with a focus on web sales will be specifically considered. A model of digital transformation of the business system for tool trading will be provided. The B2C web store will be implemented, as well as integrations with the certain components of the e-business ecosystem.